Characterization of Anammox Bacteria from Marine Water and Sediment Samples - Sudarno Utomo; Wijanarka Wijanarka; Wiharyanto Oktiawan (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Anammox activity of water and sediment taken from marine ecosistem around Semarang were investigated in anammox media agar and batch reactor. Effect of increasing salinities (3% to 5%, 7% and 9%) and decreasing salinities (3% to 2%, 1% and 0%) were  investigated. Water and sediment taken from marine ecosistem around Semarang city showed a positive result. Increasing salinity up to 9% will have a positive influence on the activity of anammox bacteria. Whereas, the decrease in salinity will negatively affect anammox bacteria. The ratio of ammonium:nitrite for anammox process ranges from 0.89 to 1.22 and ammonium removal rate varies from 0.08 to 0.59 mg-N/liter hour.